2022
DOI: 10.3390/cancers14235997
|View full text |Cite
|
Sign up to set email alerts
|

Selecting the Best Approach for the Treatment of Multiple Non-Metastatic Hepatocellular Carcinoma

Abstract: According to the Barcelona Clinic Liver Cancer (BCLC) staging system, the optimal strategy for patients with multiple HCC within the Milan Criteria is liver transplantation (LT). However, LT cannot be offered to all the patients due to organ shortages and long waiting lists, as well as because of the advanced disease carrying a high risk of poor outcomes. For early stages, liver resection (LR) or thermal ablation (TA) can be proposed, while trans-arterial chemoembolization (TACE) still remains the treatment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 106 publications
0
8
0
Order By: Relevance
“…Recent studies have already revealed how selected patients with multiple resectable HCC included in BCLC-B stage can undergo surgery better results than TACE. [6][7][8][9][10][11] Thus, latest NCCN, APASL and ESMO guidelines recommend surgery in such selected cases. However, whether LLR is safely feasible for patients with multiple HCC is still under debate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies have already revealed how selected patients with multiple resectable HCC included in BCLC-B stage can undergo surgery better results than TACE. [6][7][8][9][10][11] Thus, latest NCCN, APASL and ESMO guidelines recommend surgery in such selected cases. However, whether LLR is safely feasible for patients with multiple HCC is still under debate.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have already revealed how selected patients with multiple resectable HCC included in BCLC‐B stage can undergo surgery with better results than TACE 6–11 . Thus, latest NCCN, APASL and ESMO guidelines recommend surgery in such selected cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies comparing hepatic resection with TACE in the intermediate stage reported that OS after surgical resection was significantly better than that in the TACE groups (23.9-60% vs. 12-41.6%). 14 - 16 In addition, recent studies have also shown that liver resection has a favorable survival rate compared to non-surgical treatment in multinodular HCCs with ≤3 nodules. 4 , 14 , 18 …”
Section: Discussionmentioning
confidence: 99%